In the Shadow of the Khmer Rouge Tribunal: The Domestic Trials of Nuon Paet, Chhouk Rin and Sam Bith, and the Search for Judicial Legitimacy in Cambodia - Hall, John (Columbia Journal of Asian Law, 2006)
This paper examines the Cambodian trials of three former Khmer Rouge commanders, Nuon Paet, Sam Bith and Chhouk Rin. Between 1999 and 2006, all three were prosecuted, convicted and sentenced to life imprisonment by Cambodian civilian courts for their role in a 1994 train ambush and the subsequent kidnapping and murder of three Western backpackers. The trials are unique in the history of Cambodia, and were the first time that any commanders of the Khmer Rouge had been brought into civilian court to answer for their crimes. At a time when the Cambodian government was negotiating with the international community over the structure of the proposed United Nations-backed Khmer Rouge tribunal, the competence and independence of the Cambodian judiciary and legal system came under particular scrutiny. The trials were a crucial and timely test of the Cambodian legal system, and indeed a test of the willingness and ability of the Cambodian government to bring to justice former officers of the Khmer Rouge. As such, they mark a significant moment in the legal development of Cambodia, and represent an important step towards the creation of a functioning legal system and – at least in theory – a greater respect for legal process and for the role of an independent judiciary in that country. These domestic trials are amongst the most important legal cases to have been heard by Cambodian courts, and deserve the careful attention of the international legal community, human rights scholars and practitioners, and those interested in the rule of law and civil society generally and in Cambodia specifically.